Alexithymia and bullying behavior in students - Hikmat, Rohman; Suryani, Suryani; Yosep, Iyus; Jeharsae, Rohani (MEDISAINS, 2024)
Background: Bullying behavior among students has become a severe problem that affects their mental and physical well-being. The factors that cause bullying behavior are very complex and involve various aspects. One factor that is receiving increasing attention is alexithymia.Purpose: This study explores the relationship between alexithymia and student bullying behavior.Methods: The research used a quantitative design with a cross-sectional study approach. The research sample consisted of 120 class X students at Senior High School X in Bandung, selected using a total sampling technique. Data was collected by distributing online questionnaires, including the Toronto Alexithymia Scale-20 (TAS-20) to measure alexithymia and the Olweus Bully/Victim Questionnaire for bullying behavior. Data were analyzed using descriptive statistics and the Spearman correlation test.Results: The data obtained show that less than half of the respondents (36.7%) experienced high levels of alexithymia, 38.3% likely experienced possible alexithymia, and 25% did not experience alexithymia, while the majority of respondents exhibited high bullying behavior (43.5%). This study shows a positive relationship between alexithymia and student bullying behavior (p <0.0001; r: 0.309).Conclusion: Alexithymia can increase bullying behavior in school children. The higher the level of alexithymia, the greater the tendency to engage in bullying behavior.